Toxoplasma Effector TgIST Targets Host IDO1 to Antagonize the IFN-γ-Induced Anti-parasitic Response in Human Cells - Bando, Hironori; Sakaguchi, Naoya; Lee, Youngae; Pradipta, Ariel; Ma, Ji Su; Tanaka, Shun; Lai, De-Hua; Liu, Jianfa; Lun, Zhao-Rong; Nishikawa, Yoshifumi; Sasai, Miwa; Yamamoto, Masahiro (Frontiers in Immunology, 2018)
Toxoplasma gondii is an important human and animal pathogen that causes life-threatening toxoplasmosis. Interferon-γ (IFN-γ) is critical for anti-T. gondii cell-autonomous immunity in both humans and mice. To proliferate efficiently within the hosts, virulent strains of T. gondii can suppress IFN-γ-dependent immunity. During parasite infection, it is well-characterized that various virulence effectors are secreted to transcriptionally or post-translationally target IFN-γ-inducible GTPases, which are essential for anti-parasite responses in mice. However, the role of IFN-γ-inducible GTPases in anti-T. gondii responses in human cells is controversial since they are non-functional or absent in humans. Instead, IFN-γ-induced tryptophan degradation by indole-2,3-dioxygenase (IDO) is important for the anti-T. gondii human response. To date, the T. gondii virulent mechanism targeting IDO in human cells remains elusive. Here we show that although humans possess two IDO isozymes, IDO1 and IDO2, human cells of various origins require IDO1 but not IDO2 for IFN-γ-induced cell-autonomous immunity to T. gondii. T. gondii secretes an effector TgIST to inhibit IDO1 mRNA expression. Taken together, the data suggests that T. gondii possesses virulence programs operated by TgIST to antagonize IFN-γ-induced IDO1-mediated anti-parasite cell-autonomous immunity in human cells.